Dynamic changes of HBV markers and HBV DNA load in infants born to HBsAg(+) mothers: can positivity of HBsAg or HBV DNA at birth be an indicator for HBV infection of infants? - Chen, Tianyan (BioMed Central, 2013)
BACKGROUND: Neither HBV DNA nor HBsAg positivity at birth is an accurate marker for HBV infection of infants. No data is available for continuous changes of HBV markers in newborns to HBsAg(+) mothers. This prospective, multi-centers study aims at observing the dynamic changes of HBV markers and exploring an early diagnostic marker for mother-infant infection. METHODS: One hundred forty-eight HBsAg(+) mothers and their newborns were enrolled after mothers signed the informed consent forms. Those infants were received combination immunoprophylaxis (hepatitis B immunoglobulin [HBIG] and hepatitis B vaccine) at birth, and then followed up to 12 months. Venous blood of the infants (0, 1, 7, and 12 months of age) was collected to test for HBV DNA and HBV markers. RESULTS: Of the 148 infants enrolled in our study, 41 and 24 infants were detected as HBsAg(+) and HBV DNA(+) at birth, respectively. Nine were diagnosed with HBV infection after 7 mo follow-up. Dynamic observation of the HBV markers showed that HBV DNA and HBsAg decreased gradually and eventually sero-converted to negativity in the non-infected infants, whereas in the infected infants, HBV DNA and HBsAg were persistently positive, or higher at the end of follow-up. At 1 mo, the infants with anti-HBs(+), despite positivity for HBsAg or HBV DNA at birth, were resolved after 12 mo follow-up, whereas all the nine infants with anti-HBs(−) were diagnosed with HBV infection. Anti-HBs(−) at 1 mo showed a higher positive likelihood ratio for HBV mother-infant infection than HBV DNA and/or HBsAg at birth. CONCLUSIONS: Negativity for anti-HBs at 1 mo can be considered as a sensitive and early diagnostic indictor for HBV infection in the infants with positive HBV DNA and HBsAg at birth, especially for those infants with low levels of HBV DNA load and HBsAg titer.